SWAMEDIKASI DENGAN OBAT TRADISIONAL: STUDI EVALUATIF DI KELURAHAN CEMPANIGA, KABUPATEN MAROS - Indrayani, Ferna; Adinda Nisa Shakila (STIKES Nani Hasanuddin Makassar, 2025)
The traditional medicine is a mixture of plant materials, animal materials, mineral materials, juice preparations (jamu) that have been used for generations to overcome health issues. The research aims to determine the use of traditional medicine for self-medication in the community of Cempaniga Village, Camba District, Maros Regency. The method used was descriptive non-experimental research. The data was collected based on interview instruments, observation, and questionnaire distribution using purposive sampling method. This research was conducted on June 12 to 19, 2024 with a population of 717 people, 183 men and 534 women. The results of this study indicate that the distribution data based on age is 41-65 years as much as 56.8% with the most gender is female as much as 55.7%, where the level of knowledge is in high school as much as 79.6%, and in terms of work there are 36.3% self-employed and 83.0% married status. Meanwhile, according to the use of medicinal plants commonly used by the community, there were 16 plants that were most widely used in the leaves as much as 66.0%, with the processing method boiled as much as 63.6%, for the use of drugs taken as much as 65.4%, the rules of use 1x a day as much as 46.6%, the purpose of using drugs to cure diseases as much as 100% and the reason for using drugs because they are inexpensive as much as 61.4%. The use of traditional medicine in Cempaniga Village for self-medication with a value of 97.7% can be considered as a good category.